A Gathering light - Donnelly, Jennifer (London : A & C Black, 2006)
When mattie Gokey is given a bundle of letters to burn she fully intends to execute the wishes of the giver, Grace Brown. When Grace Brown is found drowned the next day in Big Moose Lake, Mattie finds that it is not as easy to burn those letters as she had thought. And, as she reads, a riveting story emerges - not only Grace Brown's story but also Mattie's hopes and ambitions for the future and her relationships with her friends and family.
English.
Michael L. Printz Award for Excellence in Young Adult Literature Honor Book, 2004
The Carnegie Medal, 2003.